Minimizing Energy Consumption in Roadside Unit of Zigzag Distribution Based on RS-LS Technique - Abdulrazzak H.N.; Tan N.M.L.; Mohd. Radzi N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Data transfer; Energy utilization; Intelligent systems; Process control; Roadsides; Vehicles; Communication modeling; Fixed nodes; Low density; Main chains; Minimizing energy; Roadside units; Saving energy; Vehicular ad hoc networks